Evaluation of Ghana EiA-hub and mobile app digital advisories by the Research Extension Farmer Linkage Committees (RELCs). - Jizorkuwie, Abdul-latif Baamonyor; Wilson, Michael; Danquah, Paul; Kwao, Roger; Nurudeen, Abdul-Rahman; Dalaa, Mustapha Alasan; Masoud, Jalaludeen; Kizito, Fred; Mponela, Powell (2023)
The Excellence in Agronomy is one of the initiatives of the CGIAR initiatives that contributes to Resilient Agrofood Systems. The initiative aims to deliver an increase in productivity and quality per unit of input (agronomic gain) for millions of smallholder farming households in prioritized farming systems by 2030, with an emphasis on women and young farmers, showing a measurable impact on food and nutrition security, income, resource use, soil health, climate resilience and climate change mitigation. Based on previous and ongoing research outputs and secondary data sources, the national partners including government’s research and extension agencies, and the demand partners: Degas Ltd and Ghana Agricultural Insurance Pool (GAIP) that provide inputs products, credit and market services and crop insurance, collaborated with CGIAR institutes (IITA and Alliance of Bioversity and CIAT) and co-created digital information and advisory solutions. This activity contributes to the achievement of this objective through facilitating the delivery of agronomy-at-scale solutions suppling information on climate impacts, inclusivity, and sustainability of agronomic solutions. As a first step towards validation, the Research Extension farmer Linkage Committees (RELCs) evaluated the usability of the mobile app in terms user of interface, functionality, and performance. The report provides results of the evaluation exercise by RELCs who are key in deployment of the agro-advisory, which was held at the CSIR-INSTI (Council for Scientific and Industrial Research - Institute for Scientific and Technological Information) on 16th March 2023.